2013
DOI: 10.15415/jnp.2013.11002
|View full text |Cite
|
Sign up to set email alerts
|

Surface Wear Studies in Some Materials Using α-induced Reactions

Abstract: The radio-activity produced during the irradiation of 63,65 Cu, 59 Co, 93 Nb and 121,123 Sb targets with α-particles have been measured using activation technique. The yields of radioactive isotopic products 66,67,68 Ga, 61 Cu, 96g,m Tc and 123,124,126 I have been determined in the energy range ≈ 10-40 MeV using stacked foil technique. Radioactive counting of samples was performed with a high-resolution gamma-spectrometer. As light ion beams produce an extremely narrow layer of activities in the surface o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Singh and co-workers [9] Tc and 123,124,126 I, respectively, using up to 400 nA α-particles. They suggest that the radioactive layers can be employed to study the wear rates of materials containing Cu, Co, Nb and Sb.…”
Section: Introductionmentioning
confidence: 98%
“…Singh and co-workers [9] Tc and 123,124,126 I, respectively, using up to 400 nA α-particles. They suggest that the radioactive layers can be employed to study the wear rates of materials containing Cu, Co, Nb and Sb.…”
Section: Introductionmentioning
confidence: 98%
“…Proton beams generated from cyclotrons have been widely employed to produce radionuclides relevant for medical applications [6][7][8] as well as materials studies [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors reported the competition of complete fusion (CF) and incomplete fusion (ICF) reactions at energies slightly above the Coulomb barrier [1][2][3][4][5][6][7][8][9][10], and a substantial ICF fraction has been observed at these energies. In general, the complete fusion (CF) process is considered to be the sole contributor to the total fusion cross section at low energies i.e.…”
Section: Introductionmentioning
confidence: 99%
“…High quality data for ICF processes has been obtained and reported so far worldwide [1-8, 19, 20], and conclusively demonstrate the low energy ICF, but are limited only for a few projectile-target combinations. Therefore, for better understanding of ICF dynamics, several inclusive experiments at the Inter-University Accelerator e-mail: phy.vijayraj@gmail.com e-mail: bpsinghamu@gmail.com Center (IUAC), New Delhi, India were performed by our group [5,7,8,21,22]. Based on experimental findings an attempt has been made to correlate data with suitable set of physical parameters viz., (a) projectile energy, (b) mass-asymmetry of interacting partners (µ), (c) α-Q value, and (d) input values.…”
Section: Introductionmentioning
confidence: 99%